LOGOPEDIC DOLL AS A MEANS OF CORRECTING SOUND PRONUNCIATION IN CHILDREN WITH COMBINED SPEECH DISORDERS (Psychology Travelogs, 2025)
The article reveals the concept of grammatically correct speech structure and features of the speech development of children with general underdevelopment of speech (GLD); characteristic manifestations of grammatical disorders in preschoolers with SEN and their influence on speech activity are described; the possibilities of using didactic games as an effective means of corrective work are determined.A speech therapy doll is a specially designed play tool that combines the functions of a model of an articulation apparatus and an emotionally appealing character. The use of a speech therapy doll as a means of playful interaction creates optimal conditions for the practical assimilation of speech skills formed in the process of remedial education and in the family environment. The use of a doll in the structure of didactic games requires a thorough theoretical justification and systematic study, which emphasizes its relevance and significance for speech therapy practice with children who have combined speech disorders.The development of didactic games revealed the effectiveness of specially selected game tasks aimed at consolidating certain grammatical skills, such as agreement, conjugation, and the formation of complex sentences. Games activate children's interest in learning, contribute to better learning of grammar.The effectiveness of the use of didactic games was confirmed as a result of the implementation of methodical recommendations in speech therapy work. The results of the control test showed a significant increase in the high level of grammatical correctness of speech among preschoolers, which indicates the feasibility of using games as the main method of correction. Recommendations on the use of didactic games include advice on their systematic introduction into the educational process. In particular, it is recommended to combine game tasks with other types of activities that stimulate speech activity, develop coherent speech and grammatical skills of children with SEN.It was established that game tasks contribute to the development of linguistic skills and the integration of speech skills into the educational process, increasing the motivation and involvement of children in speech activities.
Keywords: general underdevelopment of speech (STD); grammatical competence; formation of grammatically correct speech structure; gamification; word formation; word changes; linguistic units; morpheme; didactic games; game technologies; correctional work